Republic Act No. 9208 - ---, --- (Review of Women's Studies; Vol 14 No 1 (2004): Review of Women's Studies Volume XIV, Number 1 (January-June 2004))
An Act to Institute Policies to Eliminate Trafficking in Persons Especially Women and Children, Establishing the Necessary Institutional Mechanisms for the Protection and Support of Trafficked Persons, Providing Penalties for Its Violations, and for Other Purposes